Intake acoustics of naturally aspirated racing engines - Dolinar, A (Cranfield University, 2006)
The intake system is one of the components on the internal combustion engine most linked with the achievement of the high volumetric efficiency required of naturally aspirated engines. High performance racing engine intake systems have unusual geometry with separate intake pipes (often known as intake trumpets) housed in a common airbox. These intake trumpets are short pipes that are sometimes cylindrical but often conical. The flow within the intake system is very unsteady with high frequency wave action taking place. A carefully developed intake trumpet can use the wave action to tune the engine and therefore increase the performance distinctly. The intake tuning is strongly dependent on the acoustic properties of the intake system. Two important parameters are the pressure wave reflection coefficient at the open inflow end of the intake pipe (to tune the engine effectively) and the acoustic length of the intake pipe (to tune the engine at the appropriate engine speed). Acoustic measurements show that the open inflow end reflection coefficient decreases with inflow but increases with external (coaxial) flow. CFD calculations show that the vena contract a which gets created at the open inflow to the pipe disappears with coaxial flow. A conical inflow shape decreases the reflection coefficient at certain frequencies and influences the phase angle of the acoustic waves. One dimensional prediction models for the wave transfer inside these conical intake pipes are validated against acoustic measurement results. 4 The airbox decreases the reflection coefficient distinctly due to three dimensional resonances inside the airbox and limits the use of one dimensional prediction models, but the acoustic length can still be predicted accurately. Fuelling inside the intake pipe decreases the speed of sound by 10% and thus increases the acoustic pipe length. Therefore it influences the engine tuning and needs be considered when developing intake systems. A new acoustic measurement method is introduced which allows the measurement of the acoustic pipe length within the conical part of the intake pipe. Finally, the time varying nature of the intake flow and intake acoustics is explored on a running racing engine by means of hot-wire and pressure measurements and shows the influence of intake acoustics on the fluctuating intake airflow velocity especially during the period when the intake valves are closed.